Roe Protein Hydrolysates of Giant Grouper (Epinephelus lanceolatus) Inhibit Cell Proliferation of Oral Cancer Cells Involving Apoptosis and Oxidative Stress. (18th April 2016) - Yang, Jing-Iong; Tang, Jen-Yang; Liu, Ya-Sin; Wang, Hui-Ru; Lee, Sheng-Yang; Yen, Ching-Yu; Chang, Hsueh-Wei
Abstract : Roe protein hydrolysates were reported to have antioxidant property but the anticancer effects were less addressed, especially for oral cancer. In this study, we firstly used the ultrafiltrated roe hydrolysates (URH) derived from giant grouper ( Epinephelus lanceolatus ) to evaluate the impact of URH on proliferation against oral cancer cells. We found that URH dose-responsively reduced cell viability of two oral cancer cells (Ca9-22 and CAL 27) in terms of ATP assay. Using flow cytometry, URH-induced apoptosis of Ca9-22 cells was validated by morphological features of apoptosis, sub-G1 accumulation, and annexin V staining in dose-responsive manners. URH also induced oxidative stress in Ca9-22 cells in terms of reactive oxygen species (ROS)/superoxide generations and mitochondrial depolarization. Taken together, these data suggest that URH is a potential natural product for antioral cancer therapy.